Examples
Example 1 (ii)
Example 1 (iii) Important
Example 2 (i)
Example 2 (ii)
Example 2 (iii)
Example 3 Important
Example 4
Example 5 Important
Example 6 Important
Example 7 Important
Example 8 Important
Example 9 You are here
Example 10 Important
Example 11 (i)
Example 11 (ii)
Example 12
Example 13 (i) Important
Example 13 (ii)
Example 14
Example 15
Example 16 Important
Example 17 (i)
Example 17 (ii)
Example 18 (i) Important
Example 18 (ii)
Example 19 Important
Example 20 Important
Question 1 Deleted for CBSE Board 2025 Exams
Question 2 Important Deleted for CBSE Board 2025 Exams
Question 3 Deleted for CBSE Board 2025 Exams
Question 4 Important Deleted for CBSE Board 2025 Exams
Question 5 Deleted for CBSE Board 2025 Exams
Examples
Last updated at April 16, 2024 by Teachoo
Example 9 Factorize y2 – 5y + 6 by using the Factor Theorem. Step 1: We check if y2 is multiplied by 1. y2 – 5y + 6. Step 2: Writing y2 – 5y + 6.= (y – a) (y – b) So, ab = Constant term = 6 We find factors of 6 6 = 6 × 1 6 = 3 × 2 So, factors of 6 are 1, 2 and 3. We take value of y as 1 , 2, 3, –1, –2, –3, and check value of y2 – 5y + 6. Hence, a = 2 , b = 3 Now, y2 – 5y + 6.= (y – a) (y – b) = (y – 2) (y – 3)